Adsorption And Desorption Of Oxytetracyline Hydrochloride On The Activated Carbon - Nazir, Muhammad Ismathanif Md (Universiti Sains Malaysia, 2017)
The adsorption and desorption of Oxytetracycline hydrochloride (OTC HCl) onto wood-based powdered activated carbon was studied in batch equilibrium experiments. Various experimental parameters were studied including initial OTC HCl concentration (5-25 ppm), pH of the solution (3-7) and temperature of the solution (30-50). The experimental data were analysed using Langmuir and Freundlich isotherm model and the goodness of fits were checked by using linear regression coefficients (R2). It was found that, Langmuir isotherm model best represented the equilibrium data. Pseudo-first-order and pseudo-second-order kinetic model were used to analyse the kinetic data. It was found that the best fitting corresponded to the pseudo-second-order kinetic model. Various thermodynamics parameters, such as Gibbs energy, enthalpy change and entropy change, were calculated, which indicated that the present system was unspontaneous and endothermic process for OTC HCl. Based on the value of activation energy, it is also found that the adsorption mechanism was not only limited to physical adsorption but also chemisorption too for several different temperatures. The adsorption of OTC HCl on this activated carbon can be maintained above 80% across the 5 adsorption-desorption cycles and potassium chloride had been used as a desorption medium. The activated carbon was characterized by using FTIR, TGA, and surface area analyser. Other than that, the pHpzc of the activated carbon also had been identified in this experiment.